Brain-Targeted Intranasal Delivery of Zotepine Microemulsion: Pharmacokinetics and Pharmacodynamics - Sravanthi Reddy Pailla; Sunitha Sampathi; Vijayabhaskarreddy Junnuthula; Sravya Maddukuri; Sujatha Dodoala; Sathish Dyawanapelly (Pharmaceutics, 2022)
The purpose of our study was to improve the solubility, bioavailability, and efficacy of zotepine (ZTP) by brain-targeted intranasal delivery of microemulsion (ME) and its physicochemical properties, the pharmacokinetic and pharmacodynamic parameters were evaluated. The optimized ME formulations contain 10% w/w of oil (Capmul MCM C8, monoglycerides, and diglycerides of caprylic acid), 50% w/w of Smix (Labrasol and Transcutol HP, and 40% w/w of water resulting in a globule size of 124.6 ± 3.52 nm with low polydispersity index (PDI) (0.212 ± 0.013) and 2.8-fold higher permeation coefficient through porcine nasal mucosa compared to pure drug). In vitro cell line studies on RPMI 2650, Beas-2B, and Neuro-2A revealed ZTP-ME as safe. ZTP-ME administered intranasally showed higher AUC0–t24 (18.63 ± 1.33 h × µg/g) in the brain by approximately 4.3-fold than oral ME (4.30 ± 0.92 h × µg/g) and 7.7-fold than intravenous drug solutions (2.40 ± 0.36 h × µg/g). In vivo anti-schizophrenic activity was conducted using catalepsy test scores, the formulation showed better efficacy via the intranasal route; furthermore, there was no inflammation or hemorrhage in the nasal cavity. The results concluded that the ZTP microemulsion as a safe and effective strategy could greatly enhance brain distribution by intranasal administration.